Forestry assessment of sod-podzol soils’ properties in the northern part of Zhytomyr Polissya - Распопіна C. П.; Іванічева, Є. В. (Forestry and Forest Melioration, 2024)
Introduction Forest productivity depends on a complex of abiotic and biotic factors, among which soil properties are the most important. The search for relationships between forest productivity and soil properties has always been a relevant subject of scientific knowledge. The study aimed to assess the forest growth capacity of the soils in the northern part of Zhytomyr Polissia based on a comprehensive (field and analytical) investigation of the soil cover in the Olevske Forestry branch of the State Specialized Forestry Enterprise (SE) ‘Forests of Ukraine’. Materials and Methods. The forest growth capacity of the soils was assessed based on their forest growth effect, which was determined by the site class of forest stands using a set of basic soil indicators such as acidity, particle size distribution, humus content, and mobile forms of N, P, K. Results The soil cover is a variety of sod-podzolic soils of automorphic, semi-hydromorphic and soil-hydromorphic types, on which mixed (pine-birch) forests grow. In most cases, soils were formed on fluvioglacial sediments. The studied soils have a sandy composition. The content of clay particles ranges from 2.62 to 25.12% and averages 8.16±1.80%. At the same time, sandy soils predominate (94%); light loamy soils make up only 4%. A light loamy composition was identified in one plot, where sod-podzolic soils were formed on the eluvium of chalk marls. Soils are characterized by a very acidic environment and low humus and nutrients (NPK) content. The studied soils had the following average indicators: рНН2О 4.6 ± 0.36, humus content – 1.54 ± 0.48%, Nitrogen – 2.64 ± 0.59 mg per100 g of soil, Phosphorus – 2.27 ± 0.58 mg per100 g soil, Potassium – 2.73 ± 0.77 mg per 100 g soil. The exceptions are soils formed on the eluvium of chalk marls. In these soils, acidity becomes neutral (pH = 7.7), the content of mobile compounds of N and P reaches an average level (N – 4.69 mg per 100 g of soil, P2O5 – 11.6 mg per 100 g of soil), and humus and K had a very high level (humus – 2.89%, K2O 41.63 mg per 100 g of soil). Such changes in the chemical composition lead to an increase in the forest growth capacity of the sod-podzolic soil. The content of clay particles affects several properties of sod-podzolic soil, which, in turn, determine its forest potential. The content of clay particles has a linear, mathematically proven strong, and very high correlation with the content of humus and mobile compounds of K and N in the upper humus layer. For example, the correlation coefficient between the content of clay particles and the content of Nitrogen is 0.72, Potassium 0.83, and humus 0.91. The productivity of pine stands is also affected by the thickness of forest litter. Slowing down its mineralization in excessively moist habitats leads to an increase in the thickness of the litter, inhibits the biological cycle of substances, and negatively affects the tree stand nutrition which decreases forest productivity. Conclusions The stands of Pinus sylvestris have adapted to an acidic environment and low supply of soil with humus and nutrients and mainly grow according to site class I (II). Improving soil conditions leads to an increase in site class to Ia. A decrease in site class to III is explained by excessive soil moisture. Among the studied soil indicators, the contents of clay particles, humus, and mobile N and K compounds have the greatest influence on the productivity of forest stands. It was determined and mathematically substantiated that a quantitative decrease in the average values of these soil indicators leads to qualitative changes in the forest stand, in particular, to decrease its productivity from site classes I to III. 3 Figs., 2 Tables, 19 Refs.